Structured review of the patient-reported outcome instruments used in clinical trials in head and neck surgery. Issue 3 (April 2018) - Boyes, H.; Barraclough, J.; Ratansi, R.; Rogers, S.N.; Kanatas, A.
Abstract: The number of clinical trials that relate to patients with cancer of the head and neck is growing. Patient-reported outcomes, which are rarely the primary outcome, are now an important component, and in this structured review to identify and report the characteristics of the questionnaires that have been used in these trials, we summarise the findings reported. We searched several online databases using the key terms: head and neck oncology, head and neck surgery, reconstruction, clinical trials patient-reported outcomes, questionnaires, quality of life (QoL), validated instruments, and patients' satisfaction. We screened 1342 papers to collect information about the topic of the paper, sample size, selection criteria, main advantages and disadvantages of the patient-reported outcome used, and if it was used in conjunction with another measure. A total of 54 were eligible, and from them we identified 22 questionnaires. The primary reason for using a questionnaire was its relevance to the focus of the paper, such as xerostomia, pain, or swallowing. To allow the experience of patients to be the focus of the primary outcome in a clinical trial, we recommend that the measures used should be appropriate, reliable, valid, responsive, precise, interpretable, acceptable, and feasible. The trials used validated questionnaires, but the patient-reported outcome measures tended not to be the focus. There is merit in such measures being the primary outcomes in future trials and these should be designed around an explicit hypothesis.